Tun Syed Nasir, koleksi ucapan. - Nasir bin Ismail, Syed, 1921- (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1996)
The Malay language; collection of speeches by Tun Syed Nasir, 1921-1982, former head of Malaysia's Language and Literature Agency.
Includes index.
In Malay.
Keywords: Malay language -- Malaysia -- History